Metaphor and Its Role in War Room Movie - Yosua Timotius Natanael; Gina Indriani; Winema Tania; Nurma Dhona Handayani (Humanitatis : Journal of Language and Literature, 2023)
This study aims to find the types and the roles of metaphors in War Room movie. Metaphor in the movie is one of the most important aspects to understand the plot and the message of the movie. This study applied qualitative research as the design, and the observational method and non-participatory technique by Sudaryanto (2015) were conducted to collect the data. The collected data were analyzed and classified based on the theory by Levinson (1983) for the types of metaphors and Gibbs (2008) for the roles of the metaphors in talk. As the results of this research, there were 43 total metaphors found in the War Room movie. 8 metaphors have the roles in negotiating and appropriating in talk with the type of 7 predictive and 1 sentential, 10 metaphors offering a shared discourse space with 6 predictive and 4 sentential, 5 metaphors for the management of talk with 1 nominal, 3 predictive and 1 sentential, and finally 20 metaphors which bring effective impact to the talk with 2 nominal, 16 predicatives, and 2 sentential. It was also found that the metaphors in the movie were very important for the movie's plot, scenes, and message.